A two level sociological institutionalist critique of migrant workers protection: a state and regional analysis of Indonesia and the Philippines - Santoso, Anisa (2013)
This thesis examines the causes behind the slow progress of ASEAN (Association of Southeast Asian Nations) in coming up with a regional policy framework for the protection of migrant workers. I argue in this thesis that normative structures within the association and its relevant member countries do not sufficiently support the establishment of such protection policy for migrant workers at the regional level. The research puzzle is tested by taking a case study that is looking at ASEAN's major workers sending countries, Indonesia and the Philippines. At the regional level the case study includes analysis on the institution of ASEAN and the ILO as well as Malaysia as the region's main workers receiving country. I analyse this puzzle by using two level games approach and complementing the approach with the analytical framework of sociological institutionalism. Two level games approach has previously offered explanations on how domestic level politics can influence regional policy negotiations to the extent that they constrain policy makers and disturb the policy process. I utilise this analytical framework by combining it with sociological institutionalism which allows further analysis into the substance of previously mentioned constraints and how these constraints are administered. The analysis reveals that supportive ideas to migrant workers protection within the domestic institutions of Indonesia and the Philippines are not equipped with sufficient strength to overcome contradicting ideas at the regional level. Identities and discourses between societal and governmental institutions in both countries lack consolidation on the form and substance of workers protection. This subsequently constrains policy makers' actions in a regional policy formulation involving institutions at the regional level whose ideas on workers protection are contradictory. What I have also uncovered is that, although identities in ASEAN support workers protection, ASEAN's main discourses of non-interference and consensus impede the establishment of a coherent workers protection policy.